The use of infrared thermography to diagnose effects of electric shock on the brown howler monkey (Alouatta guariba) - Silva, Maraya Lincoln; Caiaffa, Mayara Grego; Teixeira, Rodrigo Hidalgo Friciello; Gonzaga, Cássia Regina Ramos; Matos, Flora Nogueira; Costa, André Luiz Mota (Neotropical Primates, 2024)
The brown howler monkey (Alouatta guariba) is a platyrrhine primate species classified as Vulnerable (VU) due to threats such as habitat loss, fragmentation, hunting and diseases. This species often persists in urbanized environments. Three free-living brown howler monkeys were treated in the veterinary hospital of Sorocaba Zoo, São Paulo state, Brazil after being subject to electrocution from electrical wires. Each individual presented different degrees of severity of electric shock. Here we describe the utility of infrared thermography to evaluate lesions and blood perfusion of tissues in monkeys affected by electric shock. Infrared thermography is a noninvasive and non-radioactive detection method that captures images of a specific body region at a distance. It has the advantage that users can avoid handling or restraint of an animal and, in some cases, it provides early detection of physiological problems. It has been widely used as a tool for examination of free-living wild animals as well as those kept under human care. In this report, infrared thermography was decisive for improving decision-making in the prognosis of the howler monkeys that initially survived electric shock.